2019
DOI: 10.1186/s13018-019-1329-0
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors for allogenic blood transfusion in total knee and hip arthroplasty

Abstract: Background Excessive blood loss in total joint arthroplasty (TJA) usually leads to an allogenic blood transfusion, which may cause adverse outcomes, prolonged length of hospitalization, and increased costs. The purpose of this study was to determine the incidence and risk factors for intraoperative and postoperative allogenic transfusion in patients undergoing primary unilateral total knee and hip arthroplasty (TKA and THA). Methods We conducted a retrospective study an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 19 publications
6
56
1
1
Order By: Relevance
“…Their relationship to transfusion has been extensively reported in previous studies. Preoperative Hb level is one of the most important predictors of postoperative transfusion in patients following TKA, for both unilateral or simultaneous bilateral TKA [1,2]. In addition, a recent study showed that preoperative Hb levels can still be used as an important predictor for postoperative transfusion in patients with TKA using antifibrinolytic drugs [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their relationship to transfusion has been extensively reported in previous studies. Preoperative Hb level is one of the most important predictors of postoperative transfusion in patients following TKA, for both unilateral or simultaneous bilateral TKA [1,2]. In addition, a recent study showed that preoperative Hb levels can still be used as an important predictor for postoperative transfusion in patients with TKA using antifibrinolytic drugs [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to perioperative blood loss, some patients require allogenic blood transfusion after TKA. The reported incidence of transfusion varies from 3.5-29.1% in TKA patients [1][2][3]. Although blood transfusion can increase the hemoglobin level and improve postoperative recovery, it is an important risk factor for many catastrophic complications, such as deep venous thrombosis [4], surgical site infection [5], and periprosthetic joint infection [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, transfusion might result in the reaction of the immune system and increase the risk of infection, and several side effects have been reported in previous studies. Thus, there is an urgent need for an effective and safe method to help reduce blood loss during surgery [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…65 years old, female gender, and BMI < 30. [23][24][25] Previous studies of various orthopaedic procedures have proposed that advanced age is a risk factor for blood transfusion, as decreased hematopoietic function of bone marrow and decreased platelet function can lead to increased blood loss. [26][27][28] In addition, physicians have traditionally used higher hemoglobin/hematocrit trigger points for transfusion in elderly patients.…”
Section: Discussionmentioning
confidence: 99%